Projected changes of ecosystem productivity and their responses to extreme heat events in northern asia - Yan, Minchu; Yue, Xu; Zhou, Botao; Sun, Xiaoling; Xin, Ning (Frontiers in Earth Science, 2022)
Change of ecosystem productivity and its response to climate extremes in the context of global warming are of great interest and particular concern for ecosystem management and adaptation. Using the simulations with and without the CO2 fertilization effect from the Yale Interactive Biosphere (YIBs) model driven by 7 CMIP5 climate models, this article investigate the future change in the gross primary productivity (GPP) of the Northern Asian ecosystem as well as the impacts from extreme heat events under the RCP2.6 and RCP8.5 scenarios, respectively. The results show an overall increase of GPP in Northern Asia during the growing season (May-September) under both scenarios, in which the CO2 fertilization effect plays a dominant role. The increases in GPP under RCP8.5 are larger than that under RCP2.6, and the greatest projected increases occur in western Siberia and Northeast China. The extreme heat events are also projected to increase generally and their influences on the Northern Asian ecosystem GPP exhibit spatiotemporal heterogeneity. Under the RCP2.6 scenario, the positive and adverse effects from the extreme heat events coexist in Northern Asia during the middle of the 21st century. During the end of the 21st century, the areas dominated by positive effects are expected to expand particularly in Northeast China and central-western Siberia. For the RCP8.5 scenario, the facilitation effects of the extreme heat events are widely distributed in Northern Asia during the middle of the 21st century, which tends to decline in both intensity and extent during the end of the 21st century. The case is similar after the CO2 fertilization effect is excluded.